Report from the committee on employment of boys in sweeping chimnies: together with the minutes of evidence taken before the committee, and an appendix (Irish University Press, 1968)
Photomechanical reprint of the ed.; N.pl., House of Commons, 1816. In: British parliamentary papers. Industrial revolution.